(untitled) (Ameghiniana, 2013)
At Divisadero Largo locality, Mendoza province, a Iarge very diverse terrestrial microflora was found. Species belonging to the genera: Accintisporites, Tenuisaccites, Sulcosaccispora, Goubinispora, cf. Striomonosaccites, Alisporites, Falcisporites, Sulcatisporites, Podocarpidites, Klausipollcnites , Chordasporites , Protodiploxypinus, Triadispora, Cedripites , Phrixipotlenit es, Microcachryidites, Protohaploxypinus, Striatoabieites, and Lueckisporites are described. The mentioned taxa constitute a quarter of the total spectrurn of palynomorphs; the remaing three quartes are represented by trilete and monolere spores, plicate, monoporate and inaperturate pollen grains. The age of this palynological assemblage is Upper Middle Triassic to Upper Triassic